A Case of Exacerbation of Chronic Pancreatitis Against the Background of COVID-19 Complicated by Pancreaticopleural Fistula with Enzymatic Pleurisy - I. I. Kotov; I. Yu. Kalinina; A. R. Propp; D. A. Sulim (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
Аim: to draw attention to the diagnosis and treatment of a rare complication of chronic pancreatitis — pancreaticopleural fistula with subtotal enzymatic exudative pleurisy, as well as the possible connection between exacerbation of chronic pancreatitis and pneumonia caused by SARS-CoV-2.Key points. In primary chronic pancreatitis, pancreaticopleural fistulas develop extremely rarely, while abdominal symptoms may not be expressed, and pleural effusion syndrome comes first in the clinical picture, so it is difficult to establish the true cause of exudative pleurisy in such a situation. The causative agent of COVID-19 has a high affinity for angiotensin-converting enzyme 2 receptors, which are present in large numbers on acinar, ductal, and secretory cells of the pancreas. Obviously, this infection can influence the course of the inflammatory process in chronic pancreatitis.This clinical observation presents a rare case of exacerbation of chronic pancreatitis with the formation of a pancreaticopleural fistula with subtotal enzymatic pleurisy on the left, which was preceded by pneumonia caused by SARS-CoV-2 in a 47-year-old man who abused alcohol. The study of exudate for amylase content helped to identify the enzymatic cause of pleurisy. Multislice computed tomography of the abdominal organs with bolus enhancement revealed a mass formation in the head of the pancreas with ectasia of the Wirsung duct and common bile duct. It was possible to restore the normal passage of bile and pancreatic secretions, as well as to stop the functioning of the pancreaticopleural fistula using pancreatoduodenal resection. A morphological examination of the macroscopic specimen revealed a diagnosis of pseudotumorous capitate chronic pancreatitis in the acute stage. After surgical treatment, according to ultrasound control, pleurisy was cured. The patient was examined a year later; his condition was consistent with the surgery. There were no clinical, physical, or instrumental data for left-sided pancreaticogenic pleurisy, hypertension of the extrahepatic and pancreatic ducts.Conclusion. Recurrent exudative pleurisy in chronic pancreatitis with rapid accumulation of exudate in a large volume with a high amylase content is a sign of pancreaticopleural fistula. The development of exacerbation of chronic pancreatitis was influenced by a combination of factors, including coronavirus infection, which suggests further accumulation of clinical material with this combination of pathological processes.